Occurrence sperm whale ambergris, mined flotilla “Slava” and “Soviet Ukraine” - Mikhalev, Yu. (Ukrainian Antarctic Journal, 2014)
The data on the occurrence of amber in sperm extracted whalers "Slava" and "Sovietskaya Ukraina" during the 1961-1978 period (22 fishing trips). The incidence was 0.35 % ambergris from sperm whales caught 43 211. Occurrence amber males (0.42%) than females (0.24%). More common black amber and less gray. Observed three cases of amber, covered large transparent crystals. Weight of pieces of amber ranged from 200 gr. to more than 100 kg. Welterweight amber at sperm was 13.0 kg, while females have significantly higher – 17.4 kg. Despite the fact that sperm whales were caught in all three oceans, the vast majority of amber found in the Indian Ocean area and its occurrence is almost coincided with the area pygmy blue whales that raises many questions.